PENGATURAN TERKAIT PENYEBARAN KARYA CIPTA KONTEN SINEMATOGRAFI YANG BERSIFAT TIDAK KOMERSIAL - Yoga Putra, A.A. Ketut; Dwijayanthi, Putri Triari (Kertha Semaya : Journal Ilmu Hukum; Vol 10 No 11 (2022), 2022)
The purpose of this study is to find out and analyze the regulations regarding the distribution of copyrighted works of cinematographic content that are non-commercial and to identify and analyze legal sanctions related to the distribution of copyrighted works of cinematographic content. This study uses a normative legal research method with a statutory approach and legal concept analysis. The results of this study explain that the act of distributing cinematographic video videos through social media that is not commercial in nature can be categorized as copyright infringement if it is done intentionally and against the law and without permission from the Creator or Copyright Holder as stipulated in the provisions of Article 9 paragraph (1) UUHC. The distribution of cinematographic video content in relation to commercial use may be carried out without permission from the Author, if the party using the Work provides compensation in the form of royalties to the Author through the Collective Management Institute. Sanctions related to the act of spreading cinematographic video content through social media itself can be categorized as a form of violation of the Creator's economic rights as referred to in Article 9 paragraph (1) especially for commercial use, can be subject to a maximum imprisonment of (four) years and/or a maximum fine of IDR 1,000,000,000.00 (one billion rupiah). Meanwhile, for economic violations of the Creator which are categorized as piracy, they are subject to a maximum imprisonment of 10 (ten) years and/or a maximum sentence of Rp. 4,000,000,000.00 (four billion rupiah).